2021
DOI: 10.1371/journal.pone.0249507
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, dynamics, and physiological races of wheat stem rust (Puccinia graminis f.sp. tritici) on irrigated wheat in the Awash River Basin of Ethiopia

Abstract: Wheat is one of the high-value major crops in the world. However, wheat stem rust is considered one of the determinant threats to wheat production in Ethiopia and the world. So this study was conducted to assess the disease intensity, seasonal distribution dynamics pattern, the genetic variability of Puccinia graminis f. sp. tritici, and to determine the virulence spectrum in the irrigated ecology of the Awash River Basin. Totally 137 wheat farms were evaluated, from 2014/15–2019/20 in six districts representi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Wheat stem rust is already a cause for concern for irrigated wheat production in northern Iraq and Kurdistan (Al-Maaroof 2017). In Ethiopia, the incidence and severity of stem rust is increasing rapidly at the lowland irrigated sites considered in this study (Yesuf et al 2021). Other studies have shown that irrigation can lead to increased meteorological suitability for a wide variety of pests and diseases (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…Wheat stem rust is already a cause for concern for irrigated wheat production in northern Iraq and Kurdistan (Al-Maaroof 2017). In Ethiopia, the incidence and severity of stem rust is increasing rapidly at the lowland irrigated sites considered in this study (Yesuf et al 2021). Other studies have shown that irrigation can lead to increased meteorological suitability for a wide variety of pests and diseases (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…Although host resistance to stem rust has generally provided adequate protection without the need for chemicals [9,16], it is important to evaluate popular commercial cultivars and other improved wheat varieties that may have the potential to replace current susceptible varieties. Recent study by [19] indicated that the races are highly virulent and affect most Sr genes except Sr31 and Sr24. From the race analysis result, TTTTF, and TKKTF have the broadest virulence spectrum race, which affects 90% of the Sr genes.…”
Section: Introductionmentioning
confidence: 99%